Transfer from primary maternity unit to tertiary hospital in New Zealand ‐ timing, frequency, reasons, urgency and outcomes: Part of the Evaluating Maternity Units study. Issue 9 (September 2015) - Grigg, Celia P.; Tracy, Sally K.; Tracy, Mark; Schmied, Virginia; Monk, Amy
Abstract Objectives to examine the transfers from primary maternity units to a tertiary hospital in New Zealand by describing the frequency, timing, reasons and outcomes of those who had antenatal or pre-admission birthplace plan changes, and transfers in labour or postnatally. Design mixed methods prospective (concurrent) cohort study, which analysed transfer and clinical outcome data (407 primary unit cohort, 285 tertiary hospital cohort), and data from the six week postpartum survey (571 respondents). Participants and setting well, pregnant women booked to give birth in a tertiary maternity hospital or primary maternity unit in one region in New Zealand (2010–2012). All women received midwifery continuity of care, regardless of their intended or actual birthplace. Results fewer than half of the women who planned a primary unit birth gave birth there (191 or 46.9%). A change of plan may have been made either antenatally or before admission in labour; and transfers were made after admission to the primary unit in labour or during the postnatal stay (about 48 hours). Of the 117 (28.5%) planning a primary unit birth who changed their planned birthplace type antenatally 73 (62.4%) were due to a clinical indication. Earthquakes accounted for 28.1% of birthplace change (during the research period major earthquakes occurred in the study region). Most (73.8%) labour changes occurred before admission in labour to the primary unit. For the 76 women who changed plan at this stage the most common reasons to do so were a rapid labour (25.0%) or prolonged rupture of membranes (23.7%). Transfers in labour from primary unit to tertiary hospital occurred for 27 women (12.6%) of whom 26 (96.3%) were having their first baby. "Slow progress" of labour accounted for 21 (77.8%) of these and 17 (62.9%) were classified as 'non-emergency'. The average transfer time for 'emergency' transfers was 58 minutes. The average time for all labour transfers from specialist consultation to birth was 4.5 hours. Nine postnatal transfers (maternal or neonatal) from a primary unit occurred (4.7%), making a total post-admission transfer rate of 17.3% for the primary unit cohort. Key conclusions birthplace changes were not uncommon, with many women changing their birthplace plan antenatally or prior to admission in labour and some transferring between facilities during or soon after birth. Most changes were due to the development of complications or 'risk factors'. Most transfers were not urgent and took approximately one hour from the decision to arrival at the tertiary hospital. Despite the transfers the neonatal clinical outcomes were comparable between both primary and tertiary cohorts, and there was higher maternal morbidity in the tertiary cohort. Implications for practice although the study size is relatively small, its comprehensive documentation of transfers has the potential to inform future research and the birthplace decision-making of childbearing women and midwives.